The influence of sodium hypochlorite concentration on the fibrin structure of human blood clots and transforming growth factor-beta 1 release: an ex vivo study - Anisha Mishra; Velmurugan Natanasabapathy; Nandini Suresh (Restorative Dentistry & Endodontics, 2022)
ObjectiveThis study investigated the effects of various concentrations of sodium hypochlorite (NaOCl) on human whole-blood clotting kinetics, the structure of the blood clots formed, and transforming growth factor (TGF)-β1 release.Materials and MethodsHuman whole blood was collected from 5 healthy volunteers and divided into 4 groups: CG (control, 0.5 mL of blood), BN0.5 (0.5 mL of blood with 0.5 mL of 0.5% NaOCl), BN3 (0.5 mL of blood with 0.5 mL of 3% NaOCl), and BN5.25 (0.5 mL of blood with 0.5 mL of 5.25% NaOCl). The effects of NaOCl on clotting kinetics, structure of fibrin and cells, and release of TGF-β1 were assessed using thromboelastography (TEG), scanning electron microscopy (SEM), and enzyme-linked immunosobent assay, respectively. Statistical analysis was conducted using the Kruskal Wallis and Mann-Whitney U tests, followed by the post hoc Dunn test. A p value < 0.05 indicated statistical significance.ResultsThe blood samples in BN0.5 and BN3 did not clot, whereas the TEG of BN5.25 showed altered clot formation. Samples from the CG and BN3 groups could only be processed with SEM, which showed that the latter lacked fibrin formation and branching of fibers, as well as clumping of red blood cells with surface roughening and distortion. TGF-β1 release was significantly highest in BN3 when all groups were compared to CG (p < 0.05).ConclusionsEach concentration of NaOCl affected the release of TGF-β1 from blood clots and altered the clotting mechanism of blood by affecting clotting kinetics and cell structure.